Difference between the surface electromyogram signals recorded from the right hand and left hand - Haibin Zeng; Ke Li; Xincheng Tian; Na Wei; Rui Song; Lelai Zhou (2017 Chinese Automation Congress (CAC), 2017)
In this paper, we aimed to investigate the difference between the surface electromyogram (sEMG) signals recorded from the right hand and left hand by means of the statistical analysis of the root mean square (RMS). Twenty-five healthy subjects participated in this experiment. For the entail 19 s recorded data of every repetition, we selected a window length of 250 ms data start from the beginning of every hand motion of the two hands. The statistical significance of most of the muscles between right hand and left hand was found in six hand motions. It indicated the lateralization of the brain in the control of these six hand motions. The average classification accuracy of the right hand (91.2 ± 0.383 %) was statistically higher than that of the left hand (90.1 ± 0.363 %) (p <; 0.05).